The prognostic role of extended preoperative hypercoagulability work-up in high-risk microsurgical free flaps: a single-center retrospective case series of patients with heterozygotic factor V Leiden thrombophilia - Falkner, Florian; Thomas, Benjamin; Aman, Martin; Risse, Eva-Maria; Wittenberg-Rump, Gerhard; Gazyakan, Emre; Harhaus-Wähner, Leila; Bigdeli, Amir Khosrow; Kneser, Ulrich; Radu, Christian Andreas (BMC surgery, 2022)
Hypercoagulability is associated with an increased risk of microvascular complications and free flap failures. The authors present their experience and approach to diagnosing and treating patients with heterozygotic factor V Leiden (hFVL) thrombophilia undergoing free flap reconstruction.
Gesehen am 13.06.2022